Interview with Mainza Mugoya from Eastern Africa Farmers' Union on population trends - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Mainza Mugoya from Eastern Africa Farmers' Union on how population trends are affecting food security. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya